Using E-Learning Technologies in Teaching and Learning Process - Jassim, Lina Lafta (Indonesian Journal Publisher in cooperation with Indonesian Social Studies Association (APRIPSI), 2020)
The Information and Communication Technologies (ICTs) use has become a major driving force in transforming education worldwide. Similarly, in the last ten years, the usage of Information and Communication Technologies and e-learning approach in Iraq has increased. Whereas, the latest educational policy of the Government of Iraq has focused on using Information and Communication Technologies and e-learning in schools and universities. The national professional standards for teachers have also suggested teachers to integrate Information and Communication Technologies in their classrooms and develop e-Learning Platforms for teaching and learning processes. However, in this study the effectiveness of Information and Communication and e-learning Technologies integration in teaching and learning has been assessed. The context selected for this research study is University of Baghdad Iraq. The research gap, which has been founded through the extensive literature review indicated that most of the students are not able to utilize Information and Communication Technologies effectively. The first objective of this study is to enable students to gain wider range of knowledge and make them enable to access internet for developing a global outlook. Moreover, the second objective of this study is to develop students’ capabilities of processing information more effectively and efficiently for teaching and learning.